A Study on the retromolar area and its clinical significance - SARAVANA KUMAR.S (International Journal of Pharma and Bio Sciences, 2019)
The retromolar foramina (RMF) is an anatomic variants in the mandible located distally to the last molar. The retromolar space (RMS), definedas a space posterior to the third molar, between the distal edge of the tooth and the anterior margin of the ascending ramus which contains Retromolar foramen. It transmits neurovascular structures that may innervate the mandibular third molar and associated tissues. Precaution is advisable in cases of unerupted third molar owing to close proximity of the retromolar foramen. The complications associated with a confirmed retromolar foramen seems to be loss of sensation in the normal distribution of the buccal nerve. Even though the retromolar foramen does not seem to be of great clinical importance, it could be a source of anxiety for the inexperienced practitioner. The Dental surgeons should be aware of this foramen and its variations, owing to the possible complication which may occur during dental implants on the lower jaw. 100 Mandibles were observed for the presence of retromolar foramen. It was found that retro molar for men was present in 28% of the mandibles, In 11 Mandible retromolar foramen was seen in right side, 9 on left side and 8 mandible showed bilateral foramen. The minimum distance of RMF from the posterior border of 3rd molar tooth ranges from 3.12mm -13.07mm on right side and 3.31mm-14.92mm on the left side. The average measurement of Temporal Crest on Right was 38.8mm where as on the left side it was found to be 40.1. The average length of the anterior border of the ramus of mandible was observed as 35.5mm on the right side and 35.7 on the left side. Likewise the measurement of the Base was seen to be average of right side 12.9mm and left side 13mm respectively.